Pendampingan Persiapan Olimpiade Matematika pada SMP Islam Darussalam Kabupaten Gowa - Nur Aisyah; Saleh, Mustakim; Adha, Isna Dia’ul; Anwar, Azwan; Agussalim, Hastuti (Pusat Riset dan Inovasi Nasional, 2026)
The application of Mastery Learning in Olympiad mentoring at Darussalam Islamic Junior High School was carried out using a classroom action research model involving 20 students from grades 8 and 9. The mentoring process followed a cyclical structure consisting of planning, action, observation, and reflection, supported by observation techniques, tests, and documentation. The implementation of the mastery learning model effectively improved students’ mathematics learning outcomes, as shown by a significant increase in mastery levels: 65% before the intervention, 75% after the first cycle, and 90% after the second cycle. In addition, the average learning score rose from 71 in the first cycle to 87 in the second cycle, reflecting substantial progress in understanding and problem-solving abilities. These results indicate that Mastery Learning not only enhances students’ mathematics performance but also strengthens their readiness and confidence to compete in the National OSN competition, demonstrating the model’s positive contribution to academic achievement and Olympiad preparation.